Advanced carbon nanotubes functionalization. (15th September 2017) - Setaro, A
Abstract: Similar to graphene, carbon nanotubes are materials made of pure carbon in its sp 2 form. Their extended conjugated π -network provides them with remarkable quantum optoelectronic properties. Frustratingly, it also brings drawbacks. The π – π stacking interaction makes as-produced tubes bundle together, blurring all their quantum properties. Functionalization aims at modifying and protecting the tubes while hindering π – π stacking. Several functionalization strategies have been developed to circumvent this limitation in order for nanotubes applications to thrive. In this review, we summarize the different approaches established so far, emphasizing the balance between functionalization efficacy and the preservation of the tubes' properties. Much attention will be given to a functionalization strategy overcoming the covalent–noncovalent dichotomy and to the implementation of two advanced functionalization schemes: (a) conjugation with molecular switches, to yield hybrid nanosystems with chemo-physical properties that can be tuned in a controlled and reversible way, and; (b) plasmonic nanosystems, whose ability to concentrate and enhance the electromagnetic fields can be taken advantage of to enhance the optical response of the tubes.